Unifying Agricultural and Environmental Ethics. Issue 3 (2nd September 2019) - Brister, Evelyn
ABSTRACT: Paul B. Thompson's agrarian ethic aims to unite the core agricultural value of providing sustenance for people with the environmental value of preserving nature into the future. His recently revised and updated book, The Spirit of the Soil, constructs a conceptual framework for evaluating normative issues in food ethics, the political economy of agriculture, and agricultural policy, as well as in environmental policy insofar as it affects agriculture. He demonstrates that the essential move in agricultural and environmental ethics is to identify systemic causes of specific problems. This makes it possible to imagine reform at the level of systems—such as economic systems, agricultural systems, and ecosystems—in a way that addresses the root causes of related problems. Thompson's work demonstrates how engaged philosophical practice can advance philosophical inquiry while at the same time having an impact on public policy.